GEOWISATA DAN WISATA EDUKASI: MERANCANG PAKET WISATA UNTUK KAWASAN RAWAN BENCANA - Wulung, Shandra Rama Panji; Andari, Rini; Kikania, Audy Putri; Abdilah, Muhammad Anthesa (PETA - Jurnal Pesona Pariwisata, 2024)
The government is currently focused on creating sustainable tourism destinations in disaster areas, with special attention given to developing geotourism as a form of educational tourism. This research aims to design educational tour packages with a geotourism theme specifically for disaster-prone areas. The study was conducted in the Tangkubanparahu Volcano disaster-prone area of North Bandung, using a combination of observations, interviews, and library documents. The data obtained was analyzed through descriptive and map analysis. The results of the research showed that geotourism has great potential as a theme for educational tourism packages in the Tangkubanparahu Volcano disaster-prone area. The 10 km route includes natural, cultural, and man-made tourist attractions which are supported by the availability of tour guides